EFFECT OF COMPOST PRODUCED WITH COW DUNG ON THE EARLY GROWTH OF Adansonia Digitata L. - Dachung, G.; Amonum, J. I.; Isaac, J. (FUDMA Journal of Sciences, 2023)
This experiment was carried out to determine the effect of different levels of compost produced with Cow dung on the early growth performance of Adansonia digitata. A. digitata seeds were planted in a seed box and transplanted into poly pots after germination with the application of compost produced with Cow dung at a rate of 1kg, 2kg and 3kg per treatment and a control experiment. This experiment was carried out in a Completely Randomized Block Design. Data on plant height, number of leaves, leave area, leave width and collar diameter were recorded. The data were collected weekly for eleven weeks starting from the second week after planting. The data collected were subjected to statistical analysis using ANOVA. Result of the experiment revealed the highest mean height (137.63±19.46) was obtained in the control experiment, highest number of leaves (17.67±2.52) was recorded at treatment 4 (3kg), The widest leaf area was recorded at treatment 3 (2kg) (77.98±2.45) and the highest mean collar diameter was recorded is obtained in the control experiment (7.25±2.05). It is deduced that, the compost from cow-dung indicates no significant improvement in the early growth performance of A. digitata; also, different rates of application have different influence on the growth of the plant. In order to obtain optimum growth and yield of A. digitata, proper soil management techniques (such as application of organic manure) should be adopted and to maintain stable soil fertility; application of compost is advisable.
Keywords: Compost; Adansonia digitata; seeds; cow dung; early growth